Akibat Hukum Putusan Perkara No.107/PDT.G/LH/2019/PNJMB terhadap Masyarakat yang Terdampak Kebakaran Hutan dan Lahan - Hendra Herman (Universitas Batanghari Jambi, 2021)
Forest and land fires cause air polution in the from of smog which can cause losses in the form of environmental damage and disruption of public health and even losses that result in loss of human life. The Ministry of Environment and Forestry has made efforts to enforce the law in the civil sector against company that carry out forest and land fires. Jambi District Court Decision Number 107/PDT. G/LH/2019/PN.JMB gives hope regrarding law enforcement in the environmental field by granting the lawsuit of the Ministry of Environment and Forestry against the company in the case PT. Agro Tumbuh Gemilang Abadi is negligent in maintaining the land in its plantation area, causing land fires. The lawsuit filed by the Ministry of Environment and Forestry has not provided a sense of justice to the community around the plantation of PT. Agro Tumbuh Gemilang Abadi affected by air pollution due to land fires. This is because in the lawsuit the Ministry of Environment and Forestry didn’t sue PT. Agro Tumbuh Gemilang Abadi to pay compensation costs to communities affected by air pollution from fires on their land. The legal consequences of this decision are that the affected community doesn’t receive compensation costs due to land fires and the community cann’t file a lawsuit against PT. Agro Tumbuh Gemilang Abadi because the Ministry of Environment and Forestry has sued PT. Agro Tumbuh Gemilang Abadi to pay for material compensation and environmental restoration costs.